The poverty of equality: a critical discourse analysis of Harrison Bergeron - Abdul Latiff, Muhamad Farid; Feisal, Hannah Suraiya (Universiti Selangor (UNISEL), 2020)
This paper makes a Critical Discourse Analysis of how Vonnegut (1961) represents power in Harrison Bergeron, a dystopian-science fiction short story that tries to achieve equality through authoritarian and cruel means. Fairclough’s (1992, 2009) Dialectical-Relational Approach was employed as the theoretical framework. The TRANSITIVITY analysis following (Halliday & Matthiessen, 2014) reveals the backgrounding of actor by the author as to hide the agency and dismiss it from any form of accountability and responsibility. On interdiscursivity, the two dominant topoi identified are the discourse of media and discourse of law.